Ignition of Particles of Wet Woody Biomass under Convective Diffusion of Water Vapor in the Near-Wall Region; Combustion, Explosion, and Shock Waves; Vol. 54, iss. 3 - Kuznetsov G. V. Geny Vladimirovich (2018, 2018)
Title screen